Biopotential of Bersama abyssinica Fresen Stem Bark Extracts: UHPLC Profiles, Antioxidant, Enzyme Inhibitory, and Antiproliferative Propensities - Kouadio Ibrahime Sinan; Annalisa Chiavaroli; Giustino Orlando; Kouadio Bene; Gokhan Zengin; Zoltán Cziáky; József Jekő; Mohamad Fawzi Mahomoodally; Marie Carene Nancy Picot-Allain; Luigi Menghini; Lucia Recinella; Luigi Brunetti; et al. (MDPI AG, 2020)
In this study, ethyl acetate, methanol, and water extracts of Bersama abyssinica (Melianthaceae) stem bark were screened for enzyme inhibitory and antioxidant properties. The water extract possessed the highest concentration of phenols (230.83 mg gallic acid equivalent/g extract), while the methanol extract was rich in flavonoids (75.82 mg rutin equivalent/g extract), and the ethyl acetate extract possessed the highest amount of saponins (97.37 mg quillaja equivalent/g). The aim of this study was to investigate the antiproliferative effects against the human colon cancer HCT116 cell line challenged with serotonin (5-HT) as a stimulating-proliferation factor. The level of HCT116 cell-deriving pool of kynurenic acid (KA) was also assessed. The UHPLC results confirmed the presence of 58, 68, and 63 compounds in the ethyl acetate, methanol, and water extracts, respectively. Mangiferin, vitexin and its isomer isovitexin were tentatively identified in all extracts and KA (m/z 190.05042 [M−H]+) was also tentatively identified in the methanol and water extracts. The methanol extract (1464.08 mg Trolox equivalent [TE]/g extract) showed the highest activity in the CUPRAC assay, whereas the water extract (1063.70 mg TE/g extract) showed the highest activity with the FRAP technique. The ethyl acetate extract was the most active acetylcholinesterase (4.43 mg galantamine equivalent/g extract) and α-glucosidase (mmol acarbose equivalent /g extract) inhibitor. The water extract was able to inhibit 5-HT-stimulated viability of HCT116 cells, and blunt 5-HT-induced reduction of cell-deriving KA. The scientific data generated in this study provide baseline data regarding the biological properties of B. abyssinica stem bark, highlighting its potential use for the development of new pharmaceutic and cosmetic agents.